Flexible IrOx neural electrode for mouse vagus nerve stimulation. (15th March 2023) - Sun, Tao; Tsaava, Téa; Peragine, Joanne; Crosfield, Christine; Lopez, Maria Fernanda; Modi, Romil; Sharma, Rohit; Li, Chunyan; Sohal, Harbaljit; Chang, Eric H.; Rieth, Loren
Abstract: Vagus nerve stimulation (VNS) is being actively explored as a treatment for multiple conditions as part of bioelectronic medicine research. Reliable and safe VNS in mouse models is a critical need for understanding mechanisms of these. We report on the development and evaluation of a microfabricated cuff electrode (MouseFlex) constructed of polyimide (PI) and with iridium oxide (IrOx) electrodes that is thermoformed to 86 µm ± 12 µm radius to interface the mouse cervical vagus nerve (r ≈ 50 µm). Innovative bench-top methods were used to evaluate the stimulation stability and electrochemical properties of electrodes. Our aggressive stimulation stability (Stim-Stab) test utilized 1 billion pulses at a 1000 Hz with a current density of 6.28 A/cm 2 (1.51 mC/cm 2 /phase) delivering 3023 × 10 3 C/cm 2 to evaluate electrode lifetimes, and all electrodes remained functional. We also investigated the effects of thermoforming on their impedance, charge storage capacity (CSC), and charge injection capacity (CIC). The modest changes in electrochemical properties indicate that the thermoforming process was well tolerated. Thermoformed electrode safety and efficacy were evaluated in-vivo by performing acute VNS in mice and monitoring their heart and respiration rate as biomarkers. Their electrochemical properties were also measured before, during and after VNS. Bradycardia and bradypnea were reliably induced at stimulation currents of 100 to 200 µA, well below the in-vivo CIC of ∼1250 µA (∼0.5 mC/cm 2 ), supporting their safety and efficacy. The electrode impedance increased and CIC decreased during in-vivo use, but largely reversed these changes in in-vitro testing after enzymatic cleaning, supporting their tolerance for surgical use. Statement of significance: Vagus nerve stimulation (VNS) is a rapidly growing aspect of healthcare and bioelectronic medicine research. Reliable and safe VNS in mice with small diameter (d ≈ 100 µm) nerves has been a challenge due to achieving intimate contact with the nerve, and the stimulation stability of commonly used electrodes. We demonstrate a microfabricated ( MouseFlex ) cuff electrode constructed of polyimide with IrOx electrodes that is thermoformed to contact the mouse cervical vagus. Bench studies highlight the stimulation stability exceeded 10 9 pulses at 6.28 A/cm 2 and their electrochemical properties were measured before, during, and after bench and nerve stimulation. Nerve stimulation induced bradycardia and bradypnea at currents below the in-vivo charge injection capacity, supporting their safety, efficacy, and tolerance for surgical handling. Graphical abstract: Image, graphical abstract